TINDAK TUTUR ASERTIF DALAM LIRIK LAGU “PERADABAN” KARYA FEAST - Putu Janita Wulandari; I Wayan Simpen; Ni Putu N. Widarsini (SOSPENDIS : Sosiologi Pendidikan dan Pendidikan IPS, 2026)
This study aims to explain the communicative function of utterances in the song lyrics “Peradaban.” The theory used in this research is Austin’s speech act theory as developed by Searle. The data used in this study are qualitative data. The data collection methods and techniques employed are the observation method with non-participatory observation (simak bebas libat cakap) and note-taking techniques. The results of the data analysis are presented using an informal method. The findings indicate that assertive speech acts in the lyrics of “Peradaban” function to express social conditions, report social phenomena, affirm the speaker’s beliefs, and convey criticism toward issues occurring in social life. Through assertive speech acts, the songwriter and singer are able to express their perspectives and evaluations of various social realities and issues within society.